A retrospective study comparing interventions by oncology and non‐oncology pharmacists in outpatient chemotherapy. Issue 4 (19th March 2021) - Kaya, Michihiro; Nakamura, Kazuyo; Nagamine, Makiko; Suyama, Yukako; Nakajo, Michiaki; Uchida, Ryo; Hagikura, Kakeru; Kanda, Ai; Sugiyama, Kyohei; Sugiyama, Rina; Nakagaki, Shigeru; Kimura, Midori
Abstract: Background: The differences in the clinical pharmacy services (CPS) provided by oncology and non‐oncology pharmacists have not been sufficiently explained. Aim: This study aimed to demonstrate the differences in direct CPS provided by oncology and non‐oncology pharmacists for patients and physicians, and to assess the potential impact of these services on medical costs. Methods: We retrospectively examined CPS provided by oncology and non‐oncology pharmacists for outpatients who underwent chemotherapy between January and December 2016. Results: In total, 1177 and 1050 CPS provided by oncology and non‐oncology pharmacists, respectively, were investigated. The rates of interventions performed by oncology and non‐oncology pharmacists for physicians‐determined treatment were 18.5% and 11.3%, respectively ( p  < .001). The rates of oncology and non‐oncology pharmacist interventions accepted by physicians were 84.6 and 78.8%, respectively ( p  = .12). Level 4 and Level 5 interventions accounted for 64.6% of all oncology pharmacist interventions and 53.0% of all non‐oncology pharmacist interventions ( p  = .03). The rates of improvement in symptoms from adverse drug reactions among patients resulting from interventions by oncology and non‐oncology pharmacists were 89.4 and 72.1%, respectively ( p  = .02). Conservative assessments of medical cost impact showed that a single intervention by an oncology and by a non‐oncology pharmacist saved ¥6355 and ¥3604, respectively. Conclusion: The results of the present study suggested that CPS by oncology pharmacists enable safer and more effective therapy for patients with cancer and indirectly contribute to reducing health care fees.